Mental health and working constraints of first-year PhD students in health and science in a French university: a cross-sectional study in the context of occupational health monitoring - Barbara Charbotel; Emmanuel Fort; Saloua Ahalli; Yamina Bridai; Nicole Baborier (BMJ Open)
Objectives To assess the mental health and working constraints perception of first-year PhD in France.Design It is a cross-sectional study.Setting The study was conducted by the team of the Lyon 1 University’s Occupational Health and Medical Service for Staff, from October 2019 to February 2020. First-year PhD students employed by the university were seen during the routine occupational health medical check-up.Participants A total of 161 PhD students in science from the 2019 intake were included in the study (participation rate 98%).Outcome measures Data were collected using a self-questionnaire on psychosocial constraints at work (Job Content Questionnaire), the quality of the professional relationship with the supervisor (Advisory Working Alliance Inventory, Student perspective (AWAI-S)), medical conditions, anxiety (Generalized Anxiety Disorder-7) and depressive symptoms (Patient Health Questionnaire-9).Results A total of 161 PhD students from the 2019 intake were included in the study (participation rate 98%). Most of the PhD students reported high psychological demands (58%), high decision latitude (53%), high social support (55%) and good professional relationships with their supervisor (mean of global score of AWAI-S=114.5). However, 34% showed signs of at least mild depression, 19% showed signs of anxiety and 20% were referred to a mental health professional after the survey. Bivariate analyses showed that history of psychiatric disorders, their relationship with their supervisor, having complementary teaching activities and stressful working conditions contributed to anxiety and depression.Conclusions Even in the first year of their PhD, some students had mental health issues. It seems relevant to generalise the medical follow-up of all PhD students as soon as they enter the doctoral programme in order to detect and treat their health problems and psychological disorders at an early stage.